An Islamic Criminal Law Study of Financial Crimes in Modern Sharia Businesses - Liantha Adam Nasution; Mhd Yadi Harahap (Fakultas Syariah Universitas Islam Negeri Sultanah Nahrasiyah Lhokseumawe, 2025)
The increasing complexity of modern finance requires a strong ethical and legal framework. Islamic law offers a foundation such as Sharia principles that can effectively curb economic violations. This study develops an integrative framework by integrating fiqh al-jinayah into corporate management and offers targeted policy recommendations. Using a normative-doctrinal methodology, this research combines a comprehensive literature review with thematic content analysis of corporate Sharia policies and a comparative examination of Sharia-compliant and non-Sharia-compliant practices. The study's findings indicate that empowering the Sharia Supervisory Board (DPS) and conducting internal Sharia audits to institutionalize the values of amanah, siddiq, and ta'zir significantly enhances transparency and accountability. These measures help prevent embezzlement, fraud, and money laundering while promoting profit-sharing financing models. The moral approach of Sharia law complements the existing legal regime by addressing the root causes of corporate misconduct, linking divine accountability with procedural rigor. The research contribution seeks to align corporate regulations by incorporating ta'zir-based sanctions for financial violations, explicitly granting the Sharia Supervisory Board (DPS) sanctioning authority, and implementing ethics-based capacity-building programs for executives and board members. This initiative paves the way for integrating Islamic legal principles into modern business processes and strengthening corporate governance with a Sharia-based value orientation.